Case studies on local mixed convection heat transfer coefficients along a radiant heated wall subjected to displacement ventilation - Camci, Muhammet; Karakoyun, Yakup; Acikgoz, Ozgen; Dalkilic, Ahmet Selim (SPRINGER, 2023)
As the demand for energy-efficient air conditioning systems enabling thermal comfort criteria increases, the research into innovative systems that combine displacement ventilation and radiant heating is being more up-to-date. This work discusses local mixed convection heat transfer coefficients over a radiant heated wall in an experimental room coupled with displacement ventilation provided by a floor level nozzle. In the experimental chamber, the air enters the room either from the floor level of the analyzed heated wall as in scenario 1 or the opposite wall in scenario 2 in the upward direction. The intervals of air inlet temperature and velocity are set between 13-27 & DEG;C and 0-2.5 ms(-1), respectively. The obtained data have been analyzed from a physical point of view, and four correlations having R-sq. numbers of 0.93, 0.94, 0.94, and 0.98 have been developed for the local mixed convective heat transfer coefficients along a heated wall. The alterations of local convection heat transfer coefficients along an examined radiant heated wall affected by a slot diffuser delivering a lowest air inlet velocity of 0.5 ms(-1) and highest air inlet velocity of 2.5 ms(-1) are gained in the intervals of 2-5.8 Wm(-2) K-1 and 2.5-10 W m(-2) K-1, in turn.
Keywords: Local convective heat transfer coefficient; Mixed convection; Radiant heated wall; Displacement ventilation; Temperature gradient; ROOM; Thermodynamics; Chemistry